Yield, cell composition, and function of islets isolated from different ages of neonatal pigs - Arefanian, Hossein; Ramji, Qahir; Gupta, Nancy; Spigelman, Aliya F.; Grynoch, Donald; MacDonald, Patrick E.; Mueller, Thomas F.; Gazda, Lawrence S.; Rajotte, Ray V.; Rayat, Gina R. (Frontiers in Endocrinology, 2022)
The yield, cell composition, and function of islets isolated from various ages of neonatal pigs were characterized using in vitro and in vivo experimental models. Islets from 7- and 10-day-old pigs showed significantly better function both in vitro and in vivo compared to islets from 3- and 5-day-old pigs however, the islet yield from 10-day-old pigs were significantly less than those obtained from the other pigs. Since islets from 3-day-old pigs were used in our previous studies and islets from 7-day-old pigs reversed diabetes more efficiently than islets from other groups, we further evaluated the function of these islets post-transplantation. B6 rag-/- mouse recipients of various numbers of islets from 7-day-old pigs achieved normoglycemia faster and showed significantly improved response to glucose challenge compared to the recipients of the same numbers of islets from 3-day-old pigs. These results are in line with the findings that islets from 7-day-old pigs showed reduced voltage-dependent K+ (Kv) channel activity and their ability to recover from post-hypoxia/reoxygenation stress. Despite more resident immune cells and immunogenic characteristics detected in islets from 7-day-old pigs compared to islets from 3-day-old pigs, the combination of anti-LFA-1 and anti-CD154 monoclonal antibodies are equally effective at preventing the rejection of islets from both age groups of pigs. Collectively, these results suggest that islets from various ages of neonatal pigs vary in yield, cellular composition, and function. Such parameters may be considered when defining the optimal pancreas donor for islet xenotransplantation studies.